Mitigation and adaptation to climate change in the conservation and preservation of the architecture and funeral lansdcape in Qubbet el Hawa, Aswan, Egypt. - Joyanes Díaz, María Dolores; Muñoz-González, Carmen María; Ruiz-Jaramillo, Jonathan; Martínez de Dios, Juan Luis; Jiménez Serrano, Alejandro (CRAterre, 2024)
On the western coast of Egypt, high-ranking officials and members of the Elephantine elite chose the east-facing hill of Qubbet el-Hawa as a cemetery. Until a few decades ago, when these tombs remained untouched, the environmental conditions inside remained constant. However, the process of exhumation and excavation of many of these tombs in the necropolis has accelerated their deterioration. Additionally, the impact of climate change, including increases in interior temperature and relative humidity, has further compounded to the problem. This research proposes a method for evalu ating the impact of future climate scenarios on the preserva tion and conservation of tombs. An experimental method was followed, combining analytical formulations and in-situ mea surements. The climate change scenarios predicted for 2030, 2050, and 2100 were based on the projected temperature vari ations. The case studies focused on the Qubbet el-Hawa tombs located in Elephantine.Data obtained from the monitoring campaign carried out in these tombs were used to validate simulation models. Design Builder, Energy Plus, and Dialux Evo software were used to generate models that replicated the tombs in detail, simulating indoor environmental conditions. One of the main conclusion of this study, is that measures to ensure the preservation and conservation of this heritage should be the reduction in fluctuations in relative air humidity and UV radiation in the interior space
https://hal.science/hal-04534448
Keywords: Qubbet el-Hawa (Egipto, Yacimiento) - Colección y conservación; Patrimonio histórico artístico - Egipto; Qubbet el Hawa; Landscape; Climate change; Preservation; Conservation; Heritage